2002
DOI: 10.1124/jpet.102.043042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dopamine Uptake Inhibition on Brain Catecholamine Levels and Locomotion in Catechol-O-methyltransferase-Disrupted Mice

Abstract: Two different uptake processes terminate the synaptic action of released catecholamines in brain: the high-affinity uptake to presynaptic nerve terminals (uptake 1 , followed by oxidation by monoamine oxidase, MAO) or glial cells uptake (uptake 2 , followed by O-methylation by catechol-O-methyltransferase, COMT, and/or oxidation by MAO). For dopaminergic neurons, uptake by the high-affinity dopamine transporter (DAT) is the most effective mechanism, and the contribution of glial COMT remains secondary under no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 39 publications
(74 reference statements)
5
56
0
Order By: Relevance
“…In outline, 10 mice (Fig. 1) The exploratory phenotype of COMT deletion was not characterized by any generic change in 'activity', as noted previously [8,10,14]. Rather, the present behavioural approach revealed reduction in rearing free and increases in sifting and chewing.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…In outline, 10 mice (Fig. 1) The exploratory phenotype of COMT deletion was not characterized by any generic change in 'activity', as noted previously [8,10,14]. Rather, the present behavioural approach revealed reduction in rearing free and increases in sifting and chewing.…”
supporting
confidence: 71%
“…Phenotypic studies in COMT knockouts have involved behavioural paradigms which include general motor activity, anxiety, aggression and sensorimotor gating [8,10,14]. Additionally, low COMT activity may fail to buffer the effect of related 22q11 mutations that also effect DA turnover in the PFC [26].…”
mentioning
confidence: 99%
“…In addition to the direct impact COMT might thus have on prefrontal functioning, different mechanisms have been pro- posed for a relationship between COMT activity and dopamine release in the basal ganglia: extrasynaptic COMT in the basal ganglia might directly influence local tonic dopaminergic activity (Huotari et al, 2002) or, alternatively, prefrontal COMT level might drive striatal dopamine levels via a regulation of glutamatergic projections from PFC to the basal ganglia (Bilder et al, 2004;Meyer-Lindenberg et al, 2006). More specifically, lower COMT level will increase firing of pyramidal neurons in the PFC and increase corticostriatal glutamate transmission, resulting finally in increased glutamatestimulated tonic dopamine release in the striatum and suppression of phasic dopamine release (Bilder et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies in the COMT knockout mice, using cocaine, GBR 12909 (a dopamine transporter inhibitor), levodopa, or amphetamine, showed that some but not all neurochemical and behavioral responses to these pharmacological challenges are sex specific (Huotari et al, 2002a(Huotari et al, , b, 2004see also O'Tuathaigh et al, 2007). For example, d-amphetamine administration affected dopamine metabolism equally in male and female knockout mice (Huotari et al, 2004), whereas hyperactivity in response to GBR 12909 was attenuated only in male mice (Huotari et al, 2002b).…”
Section: Comt and Sexual Dimorphismsmentioning
confidence: 99%